Saúde mental e web rádio : criando laços via recursos informáticos no CAPS Jatiuca - Barros, Rafael André de (2012)
This work is premised on the creation of spaces for exchange of experiences and psychological distress to users in information technology and communication, in particular, blog and web radio. Figure as a central issue the question: how users CAPS develop their role in the use of computer resources, especially in the production of web radio? The work has as objective to fulfill the analysis of production web radio as digital inclusion and examination of the relationship of users of mental health with the artifacts of web radio. Seeks to contribute through the report of this intervention and its reflections, with some possible insertion of web radio production for the field of mental health. Within a year, groups were conducted workshop production web radio with four users CAPS in psychological distress. The workshops were developed blog also with four users in monitoring the Center for Psychosocial Care (CAPS) Dr. Rostan Silvestre, in the city of Maceio - AL, in the first half of 2012. This is a qualitative research in the form of intervention research. As data collection instrument was used to record field diaries, semi-structured interviews with a multidisciplinary team of CAPS and direct observation of users, photographs and records of users. The theoretical balizou that this dissertation revolves around public policy on mental health in Brazil and Information Technology and Communication in Mental Health. Among the results, is presented in a positive manner the process of enabling social and digital inclusion in the collective production with web radio. The final product were not programs in audio, but the rediscovery of autonomy, the process of construction of subjectivity, the rediscovery of computer functionality, the discovery of a new position as interactor and protagonist of his own social status of citizens who actively participates for the exercise of their citizenship. The process of teaching and learning to use computer resources is something to be noted from the digital inclusion process. The web radio technology contributes significantly to the promotion of mental health, especially as a valuable resource in the process of social empowerment of individuals in psychological distress.